Experimental Research: The Effectiveness of Card Game Learning Media in Learning Shorof - humaini, arif (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2018)
AbstractThe word ‘media’ comes from the Latin Language ‘medium’. Media is a means of the instrument to channeling messages or learning information, by using the media can help achieve learning success. A media is very urgent and important in the effort to achieve the learning objects of the material. Learning media that is interesting for learners of Arabic is very needed, especially in understanding the material of Arabic rules. As we know that in Arabic Language Grammarly ‘Shorof’ which requires a lot of memorization. According to that as a solution is to use game as card for learning media. This learning media found in many learning process. But it has never been applied to the ‘Shorof’ material. This research was tried to experiment with its effectiveness to students of the Arabic Language Education Study Program in Faculty of Language Education, Universitas Muhammadiyah Yogyakarta. The long-term need of this research is to provide a solution or a way to facilitate Arabic learners in memorizing the rules of ‘Shorof’ material in Arabic language and find effective learning media solutions in teaching Arabic in general.Keywords: Arabic language, card, media, shorof.